URETHRAL STRICTURE MANAGED WITH HOMEOPATHIC MEDICINE: A STUDY OF FOUR CASES (Bioresearch Communications, 2022)
Urethral stricture is the narrowing of the urethral mucosa, commonly resulting from trauma followed by inflammation and fibrous changes of the corpus spongiosum along the male urethra. Clinical manifestation contains gradual deterioration of hesitancy, intermittency, dribbling of urine, and in association with a sensation of incomplete voiding of the bladder, increased frequency, urgency, straining, and urethralgia during micturition. A low Qmax in Uroflowmetry will give a primary idea of stricture; however, a Retrograde Urethrography (RUG) confirms the stricture location, length, and other identifiable pathology affecting the urethra. In this particular disease, the scope of conventional medicinal treatment is limited, however, there transurethral (dilation, internal urethrotomy) and open surgical (stricture resection and anastomosis, urethroplasty, and perineal urethrostomy) procedures are available, and recurrence is common. Homeopathic medicine is mostly an individualized medicine with a minimum number and high dilution. The use of homeopathic medicine for urological diseases is an opportunistic option. However, a group of patients with similar set of symptoms might be treated with a specific homeopathic medicine. The author is reporting a study of four urethral stricture cases treated with homeopathic medicines, namely Clematis erecta, Medorrhinum, and Aurum metallicum; within 6-24 weeks of homeopathic medicine treatment, all four patients experienced improved uroflowmetry and RUG. The current study results shows homeopathic medicine helped the patients in a harmless, cost-effective way which might encourage awareness among the medical practitioners regarding the available homeopathic medicinal treatment of urethral stricture.Bioresearch Commu. 9(1): 1245-1251, 2023 (January)